Avaliação clínica e da hepatotoxicidade do veneno de Crotalus durissus terrificus e do soro antiofídico em ratos Wistar - Pereira, Cristiane de Pauli (2012)
This study evaluated the effects of the venom from Crotalus durissus terrificus and snakebite serum on the clinical signs and liver function in 120 Wistar rats by performing physical examinations, laboratory and histopathology tests. The animals were divided into four experimental groups of thirty animals in each group. The control group (C) - received only solution of sodium chloride 0.9%; Group venom (V) - received 1mg/kg venom; Group snakebite serum (S) - received the indicated dose snakebite serum to neutralize the poison; Poison and serum group (VS) - received venom and the snakebite serum six hours later. The clinical evaluation and specimen obtained for laboratory and histological examinations were performed at time 2 hours, 8 hours and 24 hours in all groups. It was observed for the S Group elevation of serum enzyme alkaline phosphatase (FA), inflammatory reaction, changes in Kupffer cells, necrosis and hyaline degeneration; Group V heart rate decrease over time, increase in rectal temperature (TR), increased FA, increase of serum aspartate aminotransferase (AST), inflammatory infiltrate, changes in Kupffer cells, necrosis and hyaline degeneration; Group VS increased TR and also respiratory rate, elevated serum FA, AST and alanine aminotransferase (ALT), inflammatory reaction, changes in Kupffer cells, necrosis and hyaline degeneration. The results indicate that the venom and snakebite serum alter the clinical parameters and cause liver damage at the doses and times studied. However, further studies with the venom and antivenom to be able to understand the effect of time and changes in the percentage contribution of hepatotoxicity in serum isolated. In addition, to investigate the need for additional treatments to protect the liver.